Effectiveness of school-based child sexual abuse intervention among school children in the new millennium era: Systematic review and meta-analyses - Che Yusof, Ruhana; Norhayati, Mohd Noor; Mohd Azman, Yacob (Frontiers in Public Health, 2022)
Introduction School-based child sexual abuse intervention programs were developed to educate the school children to protect them from sexual abuse. The programs were evaluated to make sure the interventions were effective in reducing child sexual abuse cases (CSA). This review aimed to determine the effectiveness of the school-based child sexual abuse intervention programs in the new millennium era (2000–2021) in improving the knowledge, skills, and attitude of school children under 18 years old toward child sexual abuse. Methods A systematic search was conducted through MEDLINE (PubMed), EBSCO, and SCOPUS databases to collect full English articles related to school-based CSA intervention programs published from 2000 to 2021. Results A total of 29 studies from randomized control trial and quasi-experimental from several countries was analyzed. Comparisons within group of pre-post intervention for knowledge, skills, and attitude were measured by standardized mean difference (SMD) and 95% CI of −1.06 (95% CI: −1.29, −0.84), −0.91 (95% CI: −1.2, −0.61), and −0.51 (95% CI: −3.61, 0.58), respectively. Meanwhile for between intervention and control group comparisons, the SMD of knowledge was 0.9 (95% CI: 0.63, 1.18), skills was 0.39 (95% CI: 0.07, 0.71), and attitude was 1.76 (95% CI: 0.46, 3.07). Conclusion The programs were found to be effective in improving the knowledge, skills, and attitude of the students from pre-intervention to post-intervention and between the intervention and control groups. Systematic Review Registration:www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022312383, identifier: CRD42022312383.